Advertisement Remove all ads

# If (A − B), (B − C), (C − A) Are in G.P., Then Prove that (A + B + C)2 = 3 (Ab + Bc + Ca) - Mathematics

If (a − b), (b − c), (c − a) are in G.P., then prove that (a + b + c)2 = 3 (ab + bc + ca)

Advertisement Remove all ads

#### Solution

$\left( a - b \right), \left( b - c \right) \text { and }\left( c - a \right) \text { are in G . P} .$

$\therefore \left( b - c \right)^2 = \left( a - b \right)\left( c - a \right)$

$\Rightarrow b^2 - 2bc + c^2 = ac - bc + ab - a^2$

$\Rightarrow a^2 + b^2 + c^2 = ab + bc + ca . . . . . . . (i)$

$\text{ Now, LHS } = \left( a + b + c \right)^2 = a^2 + b^2 + c^2 + 2ab + 2bc + 2ca$

$= ab + bc + ca + 2ab + 2bc + 2ca \left[\text { Using }(i) \right]$

$= 3ab + 3bc + 3ca$

$= 3\left( ab + bc + ca \right)$

$= \text { RHS }$

Is there an error in this question or solution?
Advertisement Remove all ads

#### APPEARS IN

RD Sharma Class 11 Mathematics Textbook
Chapter 20 Geometric Progression
Exercise 20.5 | Q 12 | Page 46
Advertisement Remove all ads

#### Video TutorialsVIEW ALL [1]

Advertisement Remove all ads
Share
Notifications

View all notifications

Forgot password?